Aplikasi “Sipenting” terhadap Peningkatan Pengetahuan dan Sikap Remaja tentang Stunting - Wijaya, Andra Saferi; Annisa, Rahma (Journal of Telenursing (JOTING), 2023)
This research aims to analyze the influence of the "Sicepat" application on teenagers' knowledge and attitudes regarding stunting. The method used is quantitative research with a quasi-experimental design with a control group pretest-posttest design. The results of this study showed that there was an increase in teenagers' knowledge and attitudes regarding stunting in the intervention group and control group after being given treatment with differences in knowledge (p value=0.001) and attitudes (p value=0.000). In conclusion, the "Sicepat" application has a significant influence on increasing teenagers' knowledge and attitudes regarding stunting. Keywords: Application, Knowledge, Importance, Attitude, Stunting